Perceived Determinants Contributing to the Sustainability of Youth Broiler Farming: A Comparative Analysis between Self-Funded and Sponsored Broiler Projects - Tshikororo, Mpho; Tshikororo, Mashudu (Journal of Ecohumanism, 2024)
Sustaining agricultural production is essential to enhance food security and livelihood, particularly for rural-based societies. Broiler production has offered a lifeline for most rural inhabitants through food security and income generation, significantly contributing to their livelihood upliftment. Due to the gradual increases in demand for broiler meat and unemployment among youth, the study sought to investigate determinants that significantly contributed to the sustainability of broiler farming among youth. The study was conducted in the emerging economic zone, Thulamela municipality of Limpopo province. Simple random sampling was used to select 118 youth-owned broiler projects. The discriminant analysis method was used to draw distinct differences in determinants contributing towards the sustainability of broiler farming between self-funded and externally sponsored youth farmers. The findings revealed that most farmers within the study sample had funded their projects. Furthermore, the study findings revealed that determinants such as market linkage and mentorship significantly contributed to the sustainability of sponsored broiler farmers, while bulk buying and feed types sustained the broiler farming of self-funded farmers. The study recommended establishing suitable and cost-friendly feeds and bulk ordering to minimize transactional costs as it significantly enhances the project viability and contributes to its long-term sustainability.